Analisis Kekuatan Connecting ROD Dengan Penambahan Ukuran Dimensi - Masnurojak Bin Khanif; Pitrah Rapi Ismail; Isro Nurul Hadi; Lintang Riady Atmaja; Trisma Jaya Saputra (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the degree of change in the strength of the connecting rod test, especially on Astrea motorcycle type vehicles which have aluminum 6061 material. With design changes in the form of additional dimensions using simulations with the Autodesk Inventor 2023 application. This research was carried out by making different connecting rod designs taking into account the points fatigue of the non-ferrous aluminum metal is then tested using inventor software with pressure testing on the connecting rod where the data obtained from the results of this test is then analyzed using a static method by comparing the simulation results from the original design and the design of the connecting rod variation to obtain comparison results so that we get new values.